Lecture 26
Lecture 26
Lecture 26
Lecture # 26
Integration by substitution
This is like the Chain Rule we saw for differentiation. The idea is to integrate functions that are
composition of different functions.
d
[G (u )] = f (u )
du
Also this means that
d
∫ f (u=
)du ∫ du [G(u=
) ] du G (u ) + C
d d du du
[G=
(u ) ] [G (u )]=
⋅ f (u )
dx du dx dx
Now if we apply the integral on both sides w . r . t x we get
du d
dx ∫ [G (u ) ]=
∫ f (u ) dx = dx G (u ) + C
dx
⇒
du
∫ f (u ) dx dx = ∫ f (u )du
Example
∫ (x + 1)50 .2 x dx
2
du
Let =
u x + 1 . Then = 2x .
2
dx
Now we can rewrite the given problem as
du
∫ (x + 1)50 .2 x dx
= ∫ u = ∫u
2 50 50
dx du
dx
du
∫ f (u ) dx dx = ∫ f (u )du
u 51 ( x 2 + 1)51
∫ u du = 51 + C = 51 + C , where =u x + 1
50 2
Caution: Don’t feel tempted to just add 1 to the power 50 in the original problem!! That
will be incorrect.
The reason is that the “Power Rule” for the integrals is applicable to function which are
not a composition of others.
We want to integrate a function in which “The integrand is the derivative of a known function with a
constant added or subtracted from the independent variable”
Example
u= x + 9
du
=1 ⇒ du =
1.dx
dx
The integrand sine is the derivative of cosine function
Example
u 24 ( x − 8) 24
∫ ( x − 8) dx = ∫ u du = 24 + C = 24 + C
23 23
u =x − 8 ⇒ du =1.dx =dx
Integrand is the derivative of a known function and a constant multiplies the independent variable
Example
du 1 1 1
∫ cos(5 x=
)dx ∫ cos(u )= ∫ cos(u=
5 5
)du
5
sin(u ) =
+C
5
sin(5 x) + C
u = 5x
du
du = 5dx ⇒ = dx
5
Example
∫ sin
2
( x)cos( x)dx
So
u3 sin 3 ( x)
∫ sin ( x)cos( x)dx = ∫ u du = 3 + C = 3 + C
2 2
Example
cos x
∫ x
dx
1
Let u = x , then du = dx
2 x
So
cos x
∫ x = dx ∫ 2cos(u=
)du 2 ∫ cos(u=
)du 2sin(u ) =
+ C 2sin( x ) + C
Complicated example
∫t 3 − 5t 5 dt
43
∫t 3 − 5t 5 dt
43
u= 3 − 5t 5
1
du =−25t 4 dt ⇒ − du =t 4 dt
25
So
4
1 3
1 1 1 u
∫t − ∫ 3 u du =
3 − 5t 5 dt = − ∫ u du = − +C
43 3
25 25 25 4
3
4
3
= − (3 − 5t ) + C
5 3
100